Congenital cholesteatoma of the middle ear – uncommon clinical presentation - Bukurov, Bojana; Babić, Borivoj; Dimitrijević, Milovan; Folić, Miljan; Arsović, Nenad (Vojnosanitetski pregled, 2014)
Introduction. Congenital cholesteatoma of the middle ear is un uncommon and yet not well-defined disease. Only few cases of cholesteatoma in the fossa ovalis with unusual clinical presentation have been reported in medical literature. Case report. We reported a 16-year-old girl with congenital cholesteatoma in the fossa ovalis with minimal clinical presentation. A small mass was found occluding the fossa ovalis and mimicking otosclerotic process within tympanic cavity. The operation started as stapedotomy, and when the process was confirmed it converted to mastoidectomy via the retroauricular approach. Conclusion. The diagnosis of congenital cholesteatoma in children should always be considered, even if the clinical symptoms imitate other ear disorders, in our case otosclerosis.